Ethanol Supports Macrophage Recruitment and Reinforces Invasion and Migration of Lewis Lung Carcinoma. (October 2014) - Yu, Keke; Yang, Jinlian; Wang, Fei; Chen, Li; Lu, Yanmin; Luo, Jia; Wang, Siying
<x xml:space="preserve">Abstract</x> Background Inflammation plays a critical role in cancer progression, and our data suggested that ethanol (EtOH) could promote the progression of breast cancer via increased monocyte chemo‐attractant protein‐1 (MCP‐1). Thus, we investigated the effects of EtOH on lung cancer growth and metastasis to explore whether immunosuppression had a role. Methods C57BL/6 mice (n = 10) implanted with Lewis lung cancer (LLC) cells were used to model physiologically relevant EtOH intake on tumor growth and inflammation after macrophage polarization. Tumors were isolated and measured, and MCP‐1 expression was measured via immunohistochemistry and Western blot. Recruitment of macrophages using CD11b and F4/80 antibodies was detected with immunohistochemistry and flow cytometry. Changes in arginase I and inducible nitric oxide synthase (iNOS) expression were measured with immunofluorescent microscopy. EtOH's effect on in vitro tumor angiogenesis was evaluated in culture, and the tumor microvessel density was assessed with CD31 immunohistochemistry. Matrix metalloproteinase 9 and interleukin 10 expressions were measured by Western blot, ELISA, and immunohistochemistry. Finally, we treated a macrophage cell line RAW264.7 with EtOH and measured changes in arginase I and iNOS expression. Results With EtOH exposure, macrophage density was positively correlated with MCP‐1 expression. Macrophages infiltrated the tumor site, becoming tumor‐associated macrophages that polarized to M2 phenotypes (ArgIhigh/iNOSlow) after EtOH treatment. Cancerous cells interacted with immune cells, especially M2 macrophages, and promoted tumor angiogenesis, progression, and invasiveness. RAW264.7 cells stimulated with EtOH expressed more arginase I and less iNOS than controls. These results agreed with the features of M2 phenotype macrophages (ArgIhigh/iNOSlow). Conclusions Data show that EtOH induced M2 phenotype macrophages, suggesting that progression and metastasis of LLC may be mediated by recruitment of M2 macrophages, especially under the influence of EtOH.